Utilization of Antagonistic Interactions Between Micronutrients and Cadmium (Cd) to Alleviate Cd Toxicity and Accumulation in Crops - Muhammad Shahzad; Ayesha Bibi; Ameer Khan; Ali Shahzad; Zhengyuan Xu; Tagarika Munyaradzi Maruza; Guoping Zhang (Plants)
The presence of cadmium (Cd) in agricultural soils poses a serious risk to crop growth and food safety. Cadmium uptake and transport in plants occur through the various transporters of nutrient ions that have similar physical and chemical properties to Cd, indicating that the genetic manipulation of these transporters and agronomic improvement in the Cd-antagonistic nutrients could be a good approach for reducing Cd uptake and accumulation in crops. In this review, we discuss the interactions between Cd and some micronutrients, including zinc (Zn) and manganese (Mn), focusing on their influence on the expression of genes encoding Cd-related transporters, including ZIP7, NRAMP3, and NRAMP4. Genetic improvements in enhancing the specificity and efficiency of transporters and agronomic improvements in optimizing micronutrient nutrition can inhibit the Cd uptake and transport by these transporters. This comprehensive review provides a deep insight into genetic and agronomic improvement for fighting against Cd contamination and enhancing sustainable agricultural production.